2017
DOI: 10.21767/1791-809x.1000480
|View full text |Cite
|
Sign up to set email alerts
|

Mental Distress among Patients Admitted in Gondar University Hospital: A Cross Sectional Institution Based Study

Abstract: Background: Mental distress is a state that manifests from anxiety, depression or unexplained somatic symptoms and is typically encountered in community and health care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…In this study marital status of being married was an important factor; which was statistically associated with mental distress with almost2.7 times more positively associated with distress than being unmarried. This result of the study was similarly consistent to the study reported from Korea, Gondar University hospital, Ethiopia respectively (10,31). The reason that being married marital status more likely to develop mental distress were might be due to holding more responsibility to their home, family and child care, imbalance of demand and supply of resources to their family during being paired and poor communication and socialization relationship with in the family and other socioeconomically factors might be the possible difference.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study marital status of being married was an important factor; which was statistically associated with mental distress with almost2.7 times more positively associated with distress than being unmarried. This result of the study was similarly consistent to the study reported from Korea, Gondar University hospital, Ethiopia respectively (10,31). The reason that being married marital status more likely to develop mental distress were might be due to holding more responsibility to their home, family and child care, imbalance of demand and supply of resources to their family during being paired and poor communication and socialization relationship with in the family and other socioeconomically factors might be the possible difference.…”
Section: Discussionsupporting
confidence: 89%
“…Inpatients who drink alcohol had near to 1.7 times more likely associated with mental distress than those who were not drink alcohol. This result was extended to the study done in Australia, Gondar University hospital, Ethiopia (10,35). The reason might be resulted from people with alcohol abuse are responsible for neuropsychiatric disorders, domestic violence, child abuse and neglecting and productivity loss and also meets the diagnostic criteria for majority of mental disorders and sometimes they may develop distress in their life after a time(36).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Participants who responded eight or more items positively were regarded as having common mental illness as suggested by other studies [18][19][20][21][22]. The internal consistency of the SQR-20 scale was high (Cronbach's alpha = 0.91) in the current study.…”
Section: Data Collection Procedures and Quality Controlsupporting
confidence: 55%
“…A state of distress can be caused by many things such as poverty, unemployment, death of a loved one, a relationship break-up, medical illness or physical problems, alcohol and drug use [2,3]. As a consequence of illness, many patients face psychological challenges [4]. Tuberculosis (TB) is one of those illnesses that result in PD.…”
Section: Introductionmentioning
confidence: 99%